Comparison of the safety and efficacy of dual antiplatelet therapy versus tenecteplase in patients with minor nondisabling acute ischemic stroke - Xinzhao Jiang; Ruozhen Yuan; Jiawei Ye; Xu Wang; Zongjie Shi; Shunyuan Guo (Scientific Reports)
Abstract To evaluate the safety and efficacy of dual antiplatelet therapy (DAPT) versus tenecteplase in minor non-disabling acute ischemic stroke. This retrospective observational study utilized data from our stroke database. All consecutive patients with minor non-disabling acute ischemic stroke treated with either DAPT or tenecteplase between January 2020 and June 2023 were included in the analysis. Of the 62 patients included in the analysis, the median (IQR) age was 66 (58–76) years, and 21 patients (34%) were female. Compared with patients receiving DAPT, those treated with tenecteplase were had higher NIHSS score at treatment (median [IQR], 4 [2–5] vs. 1 [1–2]; P = 0.01). At 90 days, 74.2% of patients (23/31) in the DAPT group and 71.0% (22/31) in the tenecteplase group had an excellent functional outcome (P = 0.78). Lower proportion of patients with minor bleeding events in DAPT group than tenecteplase group (3.2% [1/31] vs. 25.8% [8/31], P = 0.01). The findings in this study show that patients presenting with minor nondisabling acute ischemic stroke within 4.5 h of symptom onset, dual antiplatelet treatment was similar to intravenous tenecteplase with regard to excellent functional outcome at 90 days. However, more proportion of patients with bleeding events treated with tenecteplase.